Analysis of Carotenoids, Vitamins and Folates in Traditional Foods from Black Sea Area - Sanches-Silva, A. (2012)
Nowadays, consumers are much more aware of nutritional composition and show especially interest in compounds with putative health benefits. Therefore, in the last few years, great attention has been devoted to the study of bioactive compounds in order to promote the consumption of traditional foods. The European project BaSeFood (Sustainable Exploitation of Bioactive Components Black Sea Area Traditional Foods) aims to study the traditional foods from the Black Sea Area, namely their nutritional and bioactive composition. In the frame of this project, the present work has analysed carotenoids, vitamins and folates in 33 traditional foods. Carotenoids and retinol and -tocopherol were extracted from samples with hexane/ethanol (4:3, v/v) and quantified by Ultra-high Pressure Liquid Chromatography (UPLC) with diode array detection (DAD). Some samples required saponification with methanolic KOH prior to chromatographic analysis. In general, the most abundant carotenoid was β-carotene. Most of the samples contain -tocopherol and do not present retinol. In order to quantify L-ascorbic acid, samples were stabilized with perchloric acid and metaphosphoric acid in ultrapure water. After dilution with mobile phase, samples were quantified by High Performance LC (HPLC)-DAD. One of the samples with highest L-ascorbic content was fruit of the evergreen cherry laurel (29.7 mg/100 g). Vitamin B2 was extracted after acid hydrolysis followed by dephosphorylation and HPLC with fluorescence detection (method EN 14152:2003, accredited according to ISO 17025). The determination of the total folate content in foodstuffs was carried out by a microbiological assay (EN 14131:2003, accredited according to ISO 17025). One of the highest vitamin B2 and total folate levels was found for roasted sunflower seeds (0.19 mg and 113 µg per 100 g of edible portion, respectively).